Membangun Karakter Unggul Melalui Pendidikan Kristiani Sebagai Upaya Gereja dalam Mewujudkan Transformasi Kristiani - Juni Wisna Zega (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2023)
Christian education is essential and crucial in building a solid character among Christians. Because of the problems that arise and are not avoided, moral degradation continues to increase. Therefore, the church's efforts in transforming Christianity and Christian education offer a profound moral and spiritual life foundation for individuals to grow in faith and develop a personality that reflects the teachings of Christ. The purpose of this study is for Christian education to be the primary tool in shaping character through teaching gospel values, fostering spiritual disciplines, and developing a supportive faith community. With a focus on building strong character, Christian education also plays a role in preparing individuals to serve and become agents of change in the church and society. Using a descriptive qualitative method, it can be concluded that Christian education is a role model for stimulating transformation in social society. First, the importance of understanding Christianity related to the theoretical study of character and its challenges. This is required so that the role of Christian education has the primary purpose of shaping character. So that it can actualize the wishes of the church in Christian education as an effort to transform Christianity